Journal Of Indonesia Economy & Bisnis = Jurnal Ekonomi & Bisnis Indonesia - Diyah Putriani (Faculty of Economic & Business Universitas Gadjah Mada, 2011)
NO. Penulis --- Judul Artikel --- Halaman 1. Diyah Putriani dan Meikha Azzani --- The Rise of China and Its Implication on Indonesia- United States Trade --- 147-157 2. Diah Setyorini Gunawan --- Convergence of GDRP Per Capita and Economic Growth Among Indonesian Provinces, 1988-2008 --- 156-175 3. Mujtahidah Anggriani Ummul Muzayyanah dan Keshav Lall Maharjan --- Livestock Products Demand in Indonesia : Choosing Between Aids and Rotterdam Demand Models --- 176-186 4. Keumala Hayati dan Indra Caniago --- Zakat Potential as A Means to Overcome Poverty (A Study in Lampung) --- 187-200 5. Mahatma Kufepaksi --- Do Overconfident Investors Trade Excessively in The Capital Market? Evidences in An Experimental Research Setting --- 201-218 6. Arika Artiningsih, M. Ridwan Novmawan, dan Sony Warsono --- Corporate Governance Implementation and Performance Asseement Using the CGCG’s UGM Rating Model : Commercial Banks in Indonesia --- 219-234 7. Sumiyana --- Accounting Fundamentals and Variations of Stock Price : Forward Looking Information Inducement --- 235-259 8. Lindrianasari, Nurdiono, dan Einde Ivana --- Accounting Performance as An Antecedent Factor of Chief Executive Officer Turnover in Indonesia --- 260-270